Relationship of Lemon Score with Prediction of Difficulty Intubation in General Anesthesia Patients - Rista, Rista; Danang Tri Yudono; Made Suandika (Java Nursing Journal, 2025)
Background: General anesthesia is the most widely practiced anesthetic technique, and mishandling of the airway may lead to serious and even life-threatening complications. Intubation success is maximized when the LEMON assessment is applied to cases where the anesthesia assessment also assesses for prediction of intubation difficulty.  Purpose: This study aims to find out the relationship between the LEMON scoring and the prediction of intubation difficulty encountered during general anesthesia. Methods: This quantitative study follows a cross-sectional design with data being collected within one single period. The sample consisted of 52 individuals undergoing general anesthesia with endotracheal intubation (ETT). Chi-square testing was performed with Fisher's Exact Test as the alternative for statistical analysis. Results: The analysis yielded a p-value of 0.019, which is below the 0.05 cutoff, demonstrating a significant association between the LEMON score and the prediction of intubation difficulty in patients undergoing general anesthesia at RSUD Dr. Soedirman Kebumen. Conclusions: A statistically significant association was found between the LEMON score and the prediction of intubation difficulty. The implication is that LEMON scoring can be another useful tool for anesthetic pre-evaluation in predicting probable airway management concerns during general anesthesia in patient.